2020
DOI: 10.1007/s11886-020-01430-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autoantibodies in Arrhythmogenesis

Abstract: Purpose of Review The role of autoantibodies in arrhythmogenesis has been the subject of research in recent times. This review focuses on the rapidly expanding field of autoantibody-mediated cardiac arrhythmias. Recent Findings Since the discovery of cardiac autoantibodies more than three decades ago, a great deal of effort has been devoted to understanding their contribution to arrhythmias. Different cardiac receptors and ion channels were identified as targets for autoantibodies, the binding of which either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…Their levels correlate with premature ventricular contraction count in ACM patients, and in vitro analyses revealed their ability to functionally affect gap junctions. This is in line with the increasingly recognized ability of autoantibodies in arrhythmia stimulation through ion channels interference [ 156 ]. Moreover, DSG2 autoantibodies may attack the desmosomes and the whole intercalated discs, further weakening these structures.…”
Section: Autoimmune Response Hypothesis In Endurance Athletessupporting
confidence: 67%
“…Their levels correlate with premature ventricular contraction count in ACM patients, and in vitro analyses revealed their ability to functionally affect gap junctions. This is in line with the increasingly recognized ability of autoantibodies in arrhythmia stimulation through ion channels interference [ 156 ]. Moreover, DSG2 autoantibodies may attack the desmosomes and the whole intercalated discs, further weakening these structures.…”
Section: Autoimmune Response Hypothesis In Endurance Athletessupporting
confidence: 67%
“…This suggests that fibrosis and calcification ensue rapidly after the start of inflammation in utero in the early second trimester, with no evidence of cardiac dysfunction or valve regurgitation on an echocardiogram. Numerous studies on animals, including murine, rat, guinea pig, and rabbit models and fetal hearts, have demonstrated that anti-Ro/SSA antibodies from mothers’ sera cause CHB by transplacental passage as early as 11 weeks of gestation [ 28 ]. Various immunohistochemistry data speculate that this leads to inhibition of the calcium channels of the fetal heart or apoptotic cell accumulation that induces macrophage infiltration and the release of cytokines, which cause fibrosis and calcification [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult AV node is thought to be more resistant to anti-SSA as it has a higher expression of calcium channels (compared with fetal AV node) 11. AV block (secondary to anti-SSA-induced inflammation) may also be reversible with immunosuppressants if caught early in the process prior to occurrence of irreversible damage 12…”
Section: Discussionmentioning
confidence: 99%